Transformational Leadership and Crisis Management Practices of Cebu Technological University-Tuburan - Maruhom, Acmad P.; Minoza, Joemar T.; Zosa, Leo T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
In making important decisions, especially during times of crisis, it is likely that leadership style cannot be disregarded (Faeq & Ismael, 2022). This study aimed at determining the transformational leadership style of school administrators and its influence to the crisis management practices of CTU as a higher education institution utilizing quantitative research focusing on descriptive survey where it used a survey questionnaire in order to describe the demographic profile to the respondents, transformational leadership style of the school administrators and the effective implementation of crisis management. Respondents were chosen using the sample determination on Slovin formula. Data were collected using the adopted questionnaire from Donmez and Toker’s (2017) and Crises Management Practices adopted from The change leader, Inc. (2007). It was revealed that age and gender are diverse, probationary employees are greater in number, new and rank and file employees dominates the workforce. Furthermore, transformational leadership styles are evident among administrators, and crisis management practices are well-implemented. Gender and civil status have no direct influence to the perceived transformational leadership styles, but age, employment status, length of service and current position does. Transformational leadership significantly influence crisis management practices in CTU-Tuburan. It can be concluded that sound decision can be made when leaders possess transformational leadership style. Hence, this calls for sustainability and consistency from the top management.